2017
DOI: 10.1017/s1368980017000891
|View full text |Cite|
|
Sign up to set email alerts
|

Processed and ultra-processed foods are associated with lower-quality nutrient profiles in children from Colombia

Abstract: Processed and ultra-processed foods generally have unhealthy nutrition profiles. Our findings suggest the categorization of foods based on processing characteristics is promising for understanding the influence of food processing on children's dietary quality. More studies accounting for the type and degree of food processing are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
59
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 20 publications
6
59
0
17
Order By: Relevance
“…UPFD provide excessive nutrients of concern including added sugar, sodium, and saturated fats and are low in fibre, protein, and micronutrients. Accordingly, studies conducted in several countries show that, when compared with people with lower consumption of UPFD, those with higher consumption have a higher risk of having diets that do not comply with one or more dietary goals recommended for the prevention of obesity . A diet based on UPFD may promote obesity also through high energy density, high glycaemic load, large portion sizes, and low content of phytochemicals …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UPFD provide excessive nutrients of concern including added sugar, sodium, and saturated fats and are low in fibre, protein, and micronutrients. Accordingly, studies conducted in several countries show that, when compared with people with lower consumption of UPFD, those with higher consumption have a higher risk of having diets that do not comply with one or more dietary goals recommended for the prevention of obesity . A diet based on UPFD may promote obesity also through high energy density, high glycaemic load, large portion sizes, and low content of phytochemicals …”
Section: Discussionmentioning
confidence: 99%
“…15 UPFD already correspond to more than 50% of total energy intake in high income countries, such as the United States 16,17 and Canada, 18 and their consumption is increasing rapidly in middleincome countries. [19][20][21][22] Consumption of UPFD has been associated with unhealthy dietary patterns [23][24][25][26][27][28][29][30] and with overweight and obesity in studies conducted in the United Kingdom, United States, Canada, Chile, Colombia, and Brazil. 13,[31][32][33][34][35][36] A longitudinal study in Latin America, that included 13 countries, found a positive, strong, and statistically significant association between annual changes in sales per capita of UPFD and annual changes in mean BMI after controlling for confounding factors.…”
mentioning
confidence: 99%
“…Few studies have assessed the energy contribution of ultraprocessed foods in children's diets, which is recognized as an important determinant of the nutritional quality of diets (Food and Agriculture Organization, ). Studies carried out with Brazilian children under 10 years old showed that about 40% (variation between 36.1% and 48.6%) of total dietary energy intake came from ultraprocessed foods (Barcelos, Rauber, & Vitolo, ; Bielemann, Santos, dos Santos Costa, Matijasevich, & Santos, ; Leite et al, ; Karnopp et al, ; Sparrenberger, Friedrich, Schiffner, Schuch, & Wagner, ; Rauber et al, ), whereas amongst Colombian children aged 5 to 12 years old, the contribution was 34.4% (Cornwell et al, ). Then, the share of ultraprocessed foods in children's diets in the United Kingdom as observed in this study was almost 1.6 times higher than those observed in the Latin American countries (Barcelos et al, ; Bielemann et al, ; Cornwell et al, ; Karnopp et al, ; Leite et al, ; Rauber et al, ; Sparrenberger et al, ), nations in which dietary patterns are based on unprocessed and minimally processed foods.…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-processed food purchasing and consumption patterns have been described in several countries [4], with studies in Brazil [17, 32-35], Chile [16, 36], Colombia [37], Indonesia [38], Kenya [39], multiple European countries [9, 40], France [41], Norway [42, 43], Sweden [44], Australia [45, 46], New Zealand [47], USA [19, 20, 48, 49], Canada [18, 50, 51], and the UK [15, 40, 52]. …”
Section: Introductionmentioning
confidence: 99%
“…In Brazil in 2008-2009, ultra-processed products contributed 25% of calories purchased [32] and 21.5% of total energy intake for adolescents and adults [33]. Among school-aged children in Colombia, 34% of energy intake came from processed and ultra-processed foods in 2011 [37]. Ultra-processed foods provided 29% of total energy intake among Chileans in 2010 [36].…”
Section: Introductionmentioning
confidence: 99%